Enhanced Optical and Thermal Stability of Blue Pyrrole Derivatives for Color Filter in Image Sensors - Sunwoo Park; Sangwook Park; Saeyoung Oh; Hyukmin Kwon; Hayoon Lee; Kiho Lee; Chun Yoon; Jongwook Park (Applied Sciences)
We designed and synthesized two novel blue pyrrole derivatives, 2-(3-cyano-4-(4-(dibutylamino)phenyl)-5-oxo-1,5-dihydro-2H-pyrrol-2-ylidene)malononitrile (BAPCP) and 2-(3-cyano-4-(4-(dihexylamino)phenyl)-5-oxo-1,5-dihydro-2H-pyrrol-2-ylidene)malononitrile (HAPCP), as potential candidates for use in image sensor color filters. The properties of these new compounds were evaluated, focusing on their optical and thermal characteristics in solution and color filter film forms. The molar extinction coefficient values of BAPCP and HAPCP in solution were 6.03 × 104 and 6.91 × 104 L/mol·cm. The molar extinction coefficient of HAPCP was 4.5 times higher than that of the commercially used Disperse Blue 359. The synthesized compounds exhibited transmittance values that meet commercial requirements, with 88.6% at 450 nm and 0.73% at 530 nm. Both newly synthesized compounds met the decomposition temperature requirement of over 230 °C, which is necessary for the manufacturing process of image sensor color filters. The decomposition temperatures of both compounds were approximately 19 °C higher than that of Disperse Blue 359. When the thermal stability of color filter films for image sensors was evaluated, BAPCP demonstrated excellent optical properties before and after thermal stability testing, maintaining its characteristics in an optimized molecular form. Accordingly, BAPCP appears to have favorable potential as a blue colorant for image sensors, attributed to its superior optical and thermal stability characteristics.